THE CORRELATION BETWEEN VOCABULARY MASTERY AND READING COMPREHENSION OF THE SEVENTH GRADE STUDENTS (English Community Journal, 2023)
This research   examined   to find out: whether or not there was correlation between vocabulary mastery and reading comprehension, among 35 students of seventh graders of junior high school. In this research used the correlation design to find out the correlation between vocabulary mastery and reading comprehension. The data was collected by documentasi and test and analyzed by using Pearson Product Moment SPSS 20. Based on the data analysis, the result indicated that the correlation between vocabulary mastery and reading comprehension (rxy) was 0.655 higher than r-table 0.373. The findings provide there was a correlation between vocabulary mastery and reading comprehension.